A Novel Self-Expanding Transcatheter Mitral Valve with Dual Annulus/Valve Diameter - Irina Yu. Zhuravleva (Journal of Functional Biomaterials, 2025)
Background: The development of transcatheter mitral valves (TMVs) represents a major advancement in cardiology, driven in part by the growing elderly population. Elderly patients frequently suffer from secondary mitral regurgitation but are often ineligible for surgical valve replacement due to high procedural risks. This study aimed to develop a self-expanding TMV stent fabricated from a single nitinol tube, featuring two distinct central zones: a smaller-diameter valve-containing segment and a larger-diameter anchoring segment for the mitral annulus. Methods: We used the COMSOL Multiphysics 6.0 software package for biotechnical engineering. Prototypes of stents and valves were manufactured in five sizes following a 22 Fr delivery system compatibility assessment and pulsatile-flow testing. Results: We bioengineered a novel stent design with an integrated porcine pericardial valve. The stents were laser-cut from nitinol tubes (4.5 mm outer diameter, 0.45 mm wall thickness) and heat-treated to achieve spatial configurations compatible with fibrous ring diameters of 40, 42, 44, 46, and 48 mm. Pericardial leaflets and coverings were then mounted onto the stents. The resulting valves were successfully loaded into a 24 Fr delivery system and exhibited proper opening and closing function under pulsatile-flow testing. Conclusions: Our findings confirm the feasibility of a single-component, dual-diameter TMV stent, offering a promising solution for high-risk patients with mitral regurgitation.